2007
DOI: 10.1007/s10653-007-9114-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of natural radioactivity in chemical fertilizer and agricultural soil: evidence of high alpha activity

Abstract: People are exposed to ionizing radiation from the radionuclides that are present in different types of natural sources, of which phosphate fertilizer is one of the most important sources. Radionuclides in phosphate fertilizer belonging to 232Th and 238U series as well as radioisotope of potassium (40K) are the major contributors of outdoor terrestrial natural radiation. The study of alpha activity in fertilizers, which is the first ever in West Bengal, has been performed in order to determine the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 15 publications
0
17
1
Order By: Relevance
“…Long-term application of phosphate fertilizers identified increase uranium content in treated soil. Physicochemical soil properties have an effect on the process of uranium migration and mobilization (Rothbaum et al 1979;Stojanović et al 2006a;Stojanović 2006b;Guzmá n et al 2006;Ghosh et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Long-term application of phosphate fertilizers identified increase uranium content in treated soil. Physicochemical soil properties have an effect on the process of uranium migration and mobilization (Rothbaum et al 1979;Stojanović et al 2006a;Stojanović 2006b;Guzmá n et al 2006;Ghosh et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The activity value of K-40 obtained from different fertilizers in this study varies from 103 to 15,606 Bq/kg. Ghosh et al (2008) indicated that the phosphate fertilizer is one of the most important contributors of natural outdoor terrestrial radiation. Continued application of phosphate fertilizer, particularly TSP, into the rice fields over a long period of time could increase the K-40 contents.…”
Section: Resultsmentioning
confidence: 99%
“…During the period of waterlogging in rice cultivation, the chemical nature of the soil can be drastically changed and pollutants can be leached easily into the subsurface, which eventually contaminate the groundwater that rural people use as a drinking water source (Chandrajith et al 2005a). Phosphate fertilizers, which are the most commonly used materials in rice fields in Sri Lanka, contribute to outdoor terrestrial natural radionuclides belonging to the 232 Th and 238 U series as well as radioisotope of potassium ( 40 K) (Ghosh et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, global changes are affected by altering the radioactivity levels in nature. Radioactivity levels can be determined by measuring any of the * corresponding author; e-mail: nnimetzaim@yahoo.com.tr characteristic radiations, such as beta-ray and gammaray radioactivity [7]. The aim of the present survey was focused on comparison of gamma-ray and beta-ray radioactivity, measured in soil samples from Edirne-Turkey.…”
Section: Introductionmentioning
confidence: 99%